PEMBINAAIU TENAGA DOSEN MIPA LPTK MELALUI PELATIHAN DALAM NEGERI - Sumarno, Mrs Utari; Saragih, Mr Robert (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 1993)
This study present a general view of inservice training dealing with the implementationof subject matter curriculum in the Teacher Education lnstitutions. The curriculum is a corecurriculum developed by the Subject Mafter Team, appointed by the Directorate Generalof Higher Education. The training was rnainly for the matriculation program {type A} atITB (Bandung lnstitute of Technology) and some advanced courses (type Bl. Data collectedfrom the trainees include some studies (i.e., type of inservice training, subject matter,educational backgrounds and positionsl. A positive result is found from 700 trainees selectedfrom 29 Teacher Education lnstitutions and who had aftended the inservice trainingin 5 locations/centers in both type A and Wpe B programs. However, some obstacles werefound also from the trainees, dealing with differences in subject matter backgrounds andEnglish proficiencies. The obstacles were also found in the inservice training including, thetime taken for discussions and repetitions of the pre-requisite materials, and the ineffectivenessof the discussions and individual works.